The Effect of Numerical Literacy Activities in Problem Based Learning Environment toward Mathematical Reasoning Ability of Elementary School Students - Nurbaya, Sitti; Sukmawati, Sukmawati; Rukli, Rukli (FKIP Universitas Lampung, 2022)
21st-century competence demands that students can reason according to current conditions that are relevant and accurate. Still, learning in the classroom uses a learning model that often does not support students’ reasoning. This study aims for differences in students’ mathematical reasoning abilities after being taught using an integrated problem-based learning model of numeracy literacy activities with students’ mathematical reasoning abilities using a problem-based learning model. This type of research is quasi-experimental design. The population is all grade IV elementary school students, Takalar. The sampling technique is cluster random sampling. The instrument uses a reasoning test. The results showed a difference in mathematical reasoning ability between students taught with an integrated problem-based learning model of numeracy literacy activities and students trained with problem-based learning. Teachers can improve students’ reasoning power by using a problem-based learning model integrated with numeracy literacy activities Keywords: Problem-based learning, numeracy literacy, reasoning, mathematics DOI: http://dx.doi.org/10.23960/jpmipa/v23i3.pp984-994